Identifying novel interruption motifs in spinocerebellar ataxia type 10 expansions. Issue 2 (2nd April 2014) - Liu, Jilin; McFarland, Karen N; Landrian, Ivette; Wu, Samuel S; Bower, Matthew; Hutter, Diane; Bushara, Khalaf; Teive, Hélio A G; Ashizawa, Tetsuo
Abstract Background and Aim Spinocerebellar ataxia type 10 (SCA10) is caused by an expansion of a normally polymorphic ATTCT repeat within intron 9 of the ATXN10 gene. Interrupting sequences in the expanded ATTCT repeat track are postulated to be a disease modifier, but are not fully characterized in SCA10 patients. As the large size and repetitive nature of the SCA10 expansion does not make it amenable for Sanger or next‐generation sequencing, we require an alternative approach to determine whether there are interrupted repeat motifs within the SCA10 expansion. Methods We developed a strategy that combines long‐range polymerase chain reaction and shot‐gun sequencing to characterize interruption sequences without full assembly of the entire disease allele. We chose three SCA10‐positive individuals with disparate clinical presentations and examined the resulting sequences for interrupting motifs. Results With this strategy, we found known heptanucleotide (ATTTTCT and ATATTCT) and pentanucleotide (ATCCC and ATCCT) interruption sequences in one allele. Additionally, we found novel pentanucleotide (ACTCT, ATTCA, ATTCC) and heptanucleotide (ATTCTCT) repeat interruption motifs in two additional samples. Conclusion The present results show the utility of this approach for determining the internal repeat structure of difficult to sequence repeat expansions. Furthermore, we find that the extent and type of interrupting sequences varies dramatically between these three SCA10‐positive individuals.